Flirtation or faceoff eaudiobook - Brunner, Leah (D.C. Eagles Hockey, 2023)
After getting my heart broken, I've sworn off athletes forever. Then my best friend has to go and marry an NHL player, and his teammate, Colby Knight, won't leave me alone. Colby is a master at scoring (on and off the ice), and he's not used to being told no. So he takes my disinterest as an invitation to pursue me even harder. I ignore him...until I realize I can use his expertise to help me get my crush's attention. But now that he's my dating coach, and we're spending so much time together, I'm growing more and more distracted. I mean, those dimples? Very enticing. Just when I think he might be more than just a playboy hockey player, a blast from the past comes back and reminds me why I swore off athletes in the first place. Can I trust Colby, or is he just another jerk who will break my heart? Trigger warnings: cheating exes; mild language